Knee kinematics and kicking distance: an IMU and OpenSim-based cross-sectional study - Wangyang Xu; Bo Gong; Xinbi Zhang; Diyan Zhang (Frontiers in Sports and Active Living)
This study aims to examine the correlation between knee joint kinematics and kicking distance in soccer players across different kicking phases. Twenty-six soccer players participated in the testing for this study. The lower limb posture data for each participant were collected using IMUs, and modeling analysis was conducted using OpenSim. During the approach phase, the extremum angle of the second knee flexion (r = 0.152, p = 0.041), as well as the ROM of the second knee extension (r = 0.169, p = 0.023) and the average angular velocity of the second knee extension (r = 0.185, p = 0.013), were positively correlated with the kicking distance. During the swing phase, the extremum angle (r = 0.178, p = 0.016) and the average angular velocity (r = 0.283, p < 0.001) of knee extension were positively correlated with the kicking distance. The findings suggest an association between specific knee kinematic patterns and the ability to achieve longer kicking distances. These kinematic patterns are characterized by: larger flexion angle during the ground contact phase of the approach; faster extension velocity and greater extension during the push-off; as well as rapid extension velocity and a larger final flexion angle during the swing.